Three-Dimensional Analysis of the Skull Base of Individuals With Cleft Lip and Palate - Mendes, Bruno Coelho [UNESP]; Silva, Kaline de Moura; da Silva, Carolina Silvano Vilarinho; Santaella, Natália Garcia; de Lima, Ana Paula da Cunha Barbosa; Borba, Alexandre Meireles; Naclério-Homem, Maria da Graça (Wolters Kluwer, 2021)
AIMS: Identify variations of skull base measurements in individuals with dentofacial deformities associated or not with cleft lip and palate and compare the results with individuals without dentofacial deformities. METHODS AND RESULTS: The individuals were categorized into three different groups: dentofacial deformity without cleft malformation, dentofacial deformity associated with cleft lip and palate, and without facial deformity. The inclusion criteria were individuals over 18 years of age, without any intervention involving facial bones or structures of interest for the study and field of view encompassing from the glabella to the hyoid bone. Poor quality CT scans or lack of adequate medical records were considered exclusion criteria. In the analysis by computerized tomography using the Dolphin Imaging Software, the length determined by the Ba-S and S-N lines was evaluated, as well as the Ba-S-N angle formed by landmarks. RESULTS: The length of S-N was not statistically different between the groups, the Ba-S length and the Ba-S-N angle demonstrated statistical difference. CONCLUSION: There was statistically significant difference in the morphometry of the (Ba-S) between groups (FS) and (C). This suggests that the standard values for cephalometric analyzes involving these structures, especially to determine the treatment planning, should be used with caution.